Occupational burnout among clinical research associates in China. (20th August 2021) - Fu, Z; Yuan, Y; Jiang, M
Abstract: Background: Clinical research associates (CRAs) play an important role in pharmaceutical research and development. Despite growing concern about occupational burnout among CRAs in China, little is known about this topic. Aims: We evaluated the factors associated with occupational burnout among CRAs in China and assessed the extent and nature of this syndrome in order to develop effective countermeasures. Methods: In October 2020, we collected data from a convenience sample of 438 CRAs from 26 major cities across China using a custom-designed questionnaire. We evaluated their psychopathological status and degree of occupational burnout based on the Maslach Burnout Inventory. Factors associated with burnout were identified using the Wilcoxon rank test, Kruskal–Wallis test, Spearman's rank correlation and multivariable ordinal logistic regression. Results: Of the 438 CRAs analyzed, 82% showed signs of occupational burnout, with a large proportion experiencing moderate burnout (50%). Burnout in Chinese CRAs manifested as emotional exhaustion (77%), depersonalization (66%) and low sense of accomplishment (15%). The severity of burnout was significantly affected by mode of working (odds ratio [OR] 1.56, 95% confidence interval [CI] 1.04–2.34), average number of working hours per week (OR 1.68, 95% CI 1.14–2.46), support provided by the hospital (OR 3.13, 95% CI 1.40–6.99) and likelihood of receiving a promotion (OR 4.05, 95% CI 1.34–12.22) (all P < 0.05). Conclusions: The incidence of occupational burnout among CRAs in China is high. Companies and hospitals must take effective measures to establish support systems for CRAs in order to alleviate this situation and thereby ensure the quality of clinical trials.